Innovative Approaches for Managing harvested irrigation water for rabi crops in Malwa region - Ranade, Deepak Hari; Choudhary, Sharad (Indian Farming, 2015)
In the Malwa region of Madhya Pradesh, after the withdrawl of monsoon rains, groundwater is used for irrigation purpose which also depletes after sometime. To overcome the problem of water scarcity in the region, storing of rain water in wells and tanks and utilizing it for irrigation is the best way out. Thus, farmers rely more on surface storage than the tube well water for irrigation.